Organizational leadership - John, Bratton (Thomson/South-Western, 2005)
This book examines the concepts, issues, and practices that comprise the core of organizational leadership from a global perspective. Underpinning its story with a mixture of description, analysis, and critique, this book achieves a distinct point of view by examining leadership through a variety of unusual prisms and by giving competing and globally diverse viewpoints equal shares in the debate